Legal Certainty for Curators in the Implementation of Auctions of Collateral Objects of Bankrupt Debtors (Case Study of Decision Number 557 K/Pdt.Sus-Pailit/2024) - Nabila Adya Trisnamurti; Amad Sudiro (Universitas Muhammadiyah Sumatera Utara, 2026)
This study investigates the legal guarantees for curators in the administration of collateral assets belonging to debtors declared bankrupt and subject to auction, as stipulated in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations (PKPU). Specifically, this study refers to Decision Number 557 K/Pdt.Sus-Pailit/2024. The discussion includes the regulatory framework regarding legal protection for curators and an examination of the curator's authority to manage collateral assets included in the bankruptcy estate to be auctioned. Using a normative juridical approach along with case studies, the evaluation is based on the application of the law and the protection of the rights of curators and creditors. The study findings indicate that the reviewed decisions confirm the curator's authority to manage and auction collateral assets as part of the bankruptcy estate resolution process. Legal clarity regarding the curator's function is crucial to ensuring that the auction process is carried out effectively, fairly, and in compliance with regulations, while protecting the rights of secured creditors.